Pengaruh Financial Knowledge dan Financial Technology Terhadap Financial Satisfaction pada Pelaku UMKM di Kabupaten Sampang - Ira Alvina Damayanti; Evaliati Amaniyah (CV. Ulil Albab Corp, 2024)
This study aims to determine the effect of financial knowledge and financial technology on the satisfaction of MSME financial actors in Sampang Regency. The method used is quantitative with a descriptive approach, involving 100 respondents through observation, interviews, and questionnaires with purposive sampling techniques. Data analysis was carried out by multiple linear regression using SPSS version 27. The results of the study showed a partial positive effect between financial knowledge and financial satisfaction, while financial technology did not have a significant effect. However, simultaneously financial knowledge and financial technology have an effect on financial satisfaction.